Association between android fat mass, gynoid fat mass and cardiovascular and all-cause mortality in adults: NHANES 2003–2007 - Ma, Wenzhi; Zhu, Huiping; Yu, Xinyi; Zhai, Xiaobing; Li, Shiyang; Huang, Nian; Liu, Keyang; Shirai, Kokoro; Sheerah, Haytham A.; Cao, Jinhong (Frontiers in Cardiovascular Medicine, 2023)
Objectives：The study of android fat mass and gynoid fat mass are still less among the predictors of mortality. This study used the NHANES database to explore the relationship between android fat mass, gynoid fat mass and CVD, all-cause mortality. Method: The study subjects were NHANES participants aged 20 and older, and two indicators of regional body composition, android fat distribution describes the distribution of human adipose tissue mainly around the trunk and upper body, in areas such as the abdomen, chest, shoulder and nape. Gynoid fat is the body fat that forms around the hips, breasts and thighs. They were measured using Dual Energy X-Ray Absorptiometry (DEXA), along with various covariates data obtained from the NHANES questionnaire and laboratory measurements, included age, gender, education, race/ethnicity, uric acid, total serum cholesterol, albumin, Vitamin C, folate, alcohol drinking, smoking status, history of diabetes, and hypertension. Mortality status was ascertained from a linked mortality file prepared by the National Center for Health Statistics. The study population was divided into four groups based on the distribution of android fat mass and gynoid fat mass by quartiles. The relationship between these two indicators and cardiovascular and all-cause mortality was investigated using Cox regression. The covariates age, gender, smoking status, drinking status, history of diabetes, and history of hypertension were stratified. Results: In the fully adjusted model, Q3 had the lowest HR in android fat mass and gynoid fat mass. When examining the relationship between android fat mass and CVD mortality, current smokers and current drinkers had the lowest CVD risk in Q2 [smoking: 0.21 (0.08, 0.52), drinking: 0.14 (0.04, 0.50)]. In diabetic patients, compared with Q1, other groups with increased android fat mass can greatly reduce the risk of CVD [Q4:0.17(0.04,0.75), Q3:0.18(0.03,1.09), Q2:0.27(0.09, 0.83)]. In ≥60 years old and female, the greater the gynoid fat mass, the smaller the HR of all-cause mortality [Q4 for ≥60 years old: 0.57(0.33,0.96), Q4 for female: 0.37(0.23,0.58)]. People <60 years old had a lower risk of all-cause mortality with gynoid fat mass in Q3 than those ≥60 years old [<60 years: 0.50 (0.27, 0.91), ≥60 years: 0.65 (0.45, 0.95)].